Transportation cost reduction for the native beef trade using the network analysis technique in Sisaket Province - Ruangchoengchum, Panutporn; Uriyapongson, Suthipong (Kasetsart Journal of Social Sciences, 2021)
This study aims to propose a method of transportation cost reduction by using network analysis in a GIS platform with Sisaket, a province in the North-Eastern region of Thailand, as the study area. This study aims to achieve the following objectives: to study the transportation processes of farmers in delivering beef cattle to cattle markets, examine the cost and constraints transporters encountered in delivering beef cattle to the markets, generate the shortest routes with conditional factors for delivering beef cattle in sub-districts (Tambon) to the closest cattle market and to propose an optimum method of reducing the transportation costs for the farmers in the entire study area. Results found that the farmers (55%) mostly preferred selling beef cattle to the merchants at their farms, whereas some of them (45%) attempted delivering their beef cattle to the markets themselves. The transporters preferred delivering within 30–50 km through smooth road surfaces with available road shoulders. The areas within 30–50 km were delineated on the map showing all potentially accessible areas around the beef cattle markets. Then, the districts (e.g. Khukhan and Kanthararom districts) require consideration to establish temporary beef cattle markets and subsequently reduce beef transportation cost.